Does a Demographic Crisis Threaten European and Polish Agriculture? - Michał Dudek; Tomasz Wojewodzic (Wieś i Rolnictwo)
In recent decades, problems in family farming have been coupled with a demographic crisis. In the face of unfavourable demographic forecasts and processes, the EU’s agricultural policy has consistently underlined the strategic importance of family farming and the need for its development as a vital segment of the economy and the core of rural communities. The paper aims to assess the grounds for policies focusing on alleviation of the demographic crisis in EU agriculture as well as giving a preliminary presentation of the effects of implementing the instrument involving subsidies for young farmers’ farms, on the example of Poland. The analyses suggest that the mechanisms for accelerating generational changes in EU agriculture have been based on questionable premises and have been not adjusted to the needs at national and regional level. In the EU policy documents and public debate, the support for generational turnover is based on arguments diagnosing a particularly adverse demographic situation in the agricultural sector. The article shows that this position is too general and unnuanced, because it does not include the general long-term population changes, other economic sectors and the different socio-economic and institutional contexts in member states, as well as being limited to a narrow range and often non-comparable public statistics. At present it is also hard to find justification for claims that instruments like subsidies for young farmers have resolved the problem of farms without successors and contributed to generational renewal in agriculture. Varied sources of data and information have been used, including EU and Polish legislation, thematic and expert studies related to demographic issues in agriculture, and empirical material gathered by public institutions.